Effects of attentional focus on the regulation of torque complexity - Philipp Bauer; João S. Gomes; João H. Oliveira; Paulo Santos; Pedro Pezarat-Correia; João R. Vaz (PLoS ONE, 2025)
Recent scientific evidence suggests that an external focus of attention (vs. an internal focus of attention) promotes a greater number of motor solutions, rendering the system more adaptable and complex. Therefore, the present study investigated the effect of the attentional focus (external vs. internal) on torque complexity and variability as well as its associated intermuscular coordination processes. Fourteen participants performed maximal and submaximal isometric knee extension tasks in three conditions (control, external focus, internal focus) to assess immediate effects of the focus of attention in a within-subjects comparison. Peak torque was extracted from maximal trials. Regarding submaximal trials, torque complexity and the magnitude of variability were assessed through Sample Entropy (SampEn), i.e., a measure of regularity in the temporal structure of torque output and coefficient of variation (CV), respectively. The intermuscular coordination was assessed through co-contraction index. An external focus led to an increase in SampEn (i.e., decreased regularity) when compared to an internal focus (p = 0.032) and a control condition (p = 0.036). Conversely, no differences were found for CV and peak torque. The external focus promoted a decrease in muscular activity of vastus medialis in comparison with the internal focus (p = 0.040) and an increase in muscular activity when compared to the control condition (p < 0.001). Furthermore, an external focus led to decreased muscular activity of semitendinosus as well as a decrease in the co-contraction indices involving semitendinosus in comparison with the internal focus and the control condition (all p < 0.05). The present findings suggest that an external focus leads to an enhanced flexibility of motor control. Moreover, the general decrease in co-contraction and in muscular activity without affecting maximal force parameters that we observed with an external focus suggest a higher efficiency of the motor system caused by intermuscular coordination processes.